Pengaruh Persepsi Kegunaan, Keamanan dan Kerahasiaan Serta Kesiapan Teknologi Informasi terhadap Intensitas Penggunaan E-Filing - Anugrah Putri Andela; Wiwit Irawati (EkoPreneur, 2020)
This study aims to see the effect of perceived usefulness, security, and confidentiality as well as information technology readiness on the intensity of e-filing usage at KPP Pratama Serpong. Quantitative Research Types. This study uses primary data where the questionnaire is taken to an individual taxpayer who lives or works in the city of South Tangerang. The sample selection uses the Nonprobability Sampling method. With the Incidental Sampling technique. The total sample used in this study was 100 samples. And data analysis was performed using SPSS Version 24. The results of this study indicate that the Usability Perception variable has a significant positive effect on the Intensity of E-filing Usage. Security and confidentiality have a significant positive effect on the intensity of e-filing use. Information technology readiness has a significant positive effect on the intensity of e-filing use.Keywords: Perceived Usability; Security and Confidentiality; Information Technology Readiness; Intensity of E-filing Usage